Undergraduates’ Behavioural Intention to use Learning Management System (LMS) to learn English: An Extended Technology Acceptance Model - Christine Shane Yik Fang, Ong (Journal of ELT, 2019)
Using the Extended Technology Acceptance Model (ETAM), this research studies the Behavioural Intention (BI) among undergraduate students in acquiring the English language through the Learning Management System (LMS). ETAM is an extension of the original Technology Acceptance Model (TAM) to include the affective variables Perceived Enjoyment (PEN) and Satisfaction (SAT), recognising Self-Directed Learning (SDL) as an exogenous variable. An online survey was conducted at a Malaysian public university, and using the data collected from the 443 respondents, statistical analysis was performed with the Variance-based Partial Least Square Structural Equation Modelling (PLS-SEM) technique and modelled using Smart PLS 3. Based on the findings, all indicators of the measurement model were able to achieve convergent and discriminant validity. Three of the sixteen hypotheses were not supported. SDL was found to have a significant effect on cognitive variables Perceived Usefulness (PU) and Perceived Ease of Use (PEU), affective variables PEN and SAT and endogenous variables BI. PU and PEU had negative relationships with BI. PEN was shown to have an indirect effect between PU and BI while SAT did not mediate between PEU and BI. This study also looked into how higher education stakeholders could improve and sustain online learning systems in Malaysia. This research concludes with some recommendations and directions for future TAM-related research.